1997
DOI: 10.1056/nejm199708143370701
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Changes in the Consumption of Macrolide Antibiotics on Erythromycin Resistance in Group A Streptococci in Finland

Abstract: In Finland, after nationwide reductions in the use of macrolide antibiotics for outpatient therapy, there was a significant decline in the frequency of erythromycin resistance among group A streptococci isolated from throat swabs and pus samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
532
2
33

Year Published

1999
1999
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,060 publications
(590 citation statements)
references
References 19 publications
16
532
2
33
Order By: Relevance
“…Uma nova cepa de Staphylococcus aureus resistente à meticilina, adquirida na comunidade, tem sido descrita 78 , com propriedades diferentes das cepas adquiridas no hospital com esta caracterís-tica. A prevalência de microrganismos resistentes aos macrolídeos [79][80][81] e cefalosporinas 82 tem aumentado nas regiões com grande utilização de macrolídeos. Em geral, o planejamento da terapêutica antimicrobiana não deve ser baseado apenas no conhecimento do organismo mais provável numa determinada faixa etária e na gravidade da doença, mas também com informações acerca dos padrões locais de resistência aos antimicrobianos.…”
Section: Padrões De Resistência Aos Antimicrobianosunclassified
“…Uma nova cepa de Staphylococcus aureus resistente à meticilina, adquirida na comunidade, tem sido descrita 78 , com propriedades diferentes das cepas adquiridas no hospital com esta caracterís-tica. A prevalência de microrganismos resistentes aos macrolídeos [79][80][81] e cefalosporinas 82 tem aumentado nas regiões com grande utilização de macrolídeos. Em geral, o planejamento da terapêutica antimicrobiana não deve ser baseado apenas no conhecimento do organismo mais provável numa determinada faixa etária e na gravidade da doença, mas também com informações acerca dos padrões locais de resistência aos antimicrobianos.…”
Section: Padrões De Resistência Aos Antimicrobianosunclassified
“…Thus, once resistant strains have become established in a population, the problem may not always be reversible, although some studies have indicated a decline in prevalence after intervention. 16,18,19 By contrast with most other countries in Europe, no increase of antibiotic resistance among invasive pneumococcal isolates in Sweden has been reported since 2000. 20 The frequency of PNSP in invasive isolates has varied between 2·5% and 5·0% and the number of invasive erythromycin-resistant pneumococci has not increased between 1999 and 2005.…”
Section: Pneumococcal Infectionmentioning
confidence: 99%
“…This is often the case in pathogenic populations (Foweraker et al, 2005;Fothergill et al, 2010;Workentine et al, 2013) because of spatial heterogeneity of drug concentrations (Baquero and Negri, 1997), historical exposure to antibiotics followed by immigration or mutation (Seppälä et al, 1997;Scanvic-Hameg et al, 2002) or the inherently high genetic diversity in chronic infections (Oliver et al, 2000(Oliver et al, , 2004. Natural populations are also genetically diverse in terms of drug resistance (D'Costa et al, 2006;Martinez, 2009).…”
Section: Introductionmentioning
confidence: 99%